Spans in South Caucasian agreement: Revisiting the pieces of inflection - Blix, Hagen (Natural language and linguistic theory, 2021)
I argue that a range of morphological phenomena sensitive to features of multiple arguments in Georgian (South Caucasian)—including Anti-Superiority effects (Béjar 2003), and omnivorous number effects (Nevins 2011)–receive a unified account if spellout targets contiguous spans of maximally simple heads, in a fixed hierarchy. I introduce new data from a related language, Laz, and show that a close comparison of the two languages reveals that (i) number agreement is expressed omnivorously only if the prefix is not sensitive to number, and that (ii) this number expression covaries with Tense only if the subject is third person. I argue that both Anti-Superiority and the facts about number expression should be interpreted as fusional morphology being limited to third person contexts, and that a principled explanation for such an asymmetry can be provided, if first and second person structurally contain third person, and the matching of exponents with syntactic structure is governed by Overspecification (Starke 2009), such that a lexicalized span is a candidate of spellout for its sub-spans.